Household behavior in the presence of economic crisis: evidence from Argentina, 2002 - Fiszbein, Ariel (2003)
At the end of 2001, Argentina suffered one of its worst economic crises in memory. When presented with lower incomes, reduced employment, and other economic shocks, households have responded by adjusting their consumer behavior and adopting a number of coping strategies. In this paper, we use evidence from a household survey completed at the time of the Argentine crisis to examine whether the use of coping strategies is directly linked to the type of shock experienced by the household and whether household behavior varies by wealth or family type.